Influência da construção de usina hidrelétrica (uhe) sobre a comunidade de acroinvertebrados bentônicos em um rio neotropical - Nunes, Tielli de Fátima (2023)
This study aimed to assess the influences of environmental changes generated by the installation of a hydroelectric power plant on the benthic macroinvertebrate community in a neotropical river, as well as to observe possible alterations in taxonomic composition and functional attributes in the pre and post-implementation periods of the Hydroelectric Power Plant (HPP). Benthic organism samples were collected using a Petersen grab and were conducted monthly from October 2016 to December 2018, corresponding to the pre-reservoir filling period, and from January 2019 to October 2020, corresponding to the post-filling period. After collection, the samples were preserved in 70% alcohol and the organisms were identified using appropriate keys and references. Data analysis was performed using statistical tests and multivariate analyses. Relative abundances, species richness, Shannon diversity indices (H'), and Pielou evenness (J') were calculated. Abundance data for species and environmental variables were subjected to tests for normality and homoscedasticity. Subsequently, a permutational multivariate dispersion test was conducted. To test the dataset of relative abundance of functional groups, the Shapiro-Wilk test and Bartlett test were used, followed by a Permanova analysis with standardized data. Principal component analysis (PCA) was used to determine the environmental variables that most influenced the distribution of data variance. The IndVal test was performed to identify indicator species, and all analyses were conducted using the R program. Organisms belonging to 94 taxa were captured, distributed across the phyla Nematoda, Mollusca, Annelida, and Arthropoda. The highest occurrences were recorded for Chironomidae and Oligochaeta in both sampling periods. Considering functional groups, substantial alterations in occurrences were observed between the assessed periods and rivers. The Permanova for the groups resulted in a non-significant outcome, indicating homogeneity in group dispersion. Environmental variables, including electrical conductivity, COD, and total solids, increased in the post-closure period in both upstream and downstream dammed rivers, while turbidity decreased. Ammonium and organic nitrogen values increased in the post-closure period only in the dammed rivers. The IndVal test identified a total of 12 distinct indicator species. This study concludes that the construction of a hydroelectric power plant can have significant impacts on the benthic macroinvertebrate community in a neotropical river.